-2(x-5)=4*4

Simple and best practice solution for -2(x-5)=4*4 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -2(x-5)=4*4 equation:


Simplifying
-2(x + -5) = 4 * 4

Reorder the terms:
-2(-5 + x) = 4 * 4
(-5 * -2 + x * -2) = 4 * 4
(10 + -2x) = 4 * 4

Multiply 4 * 4
10 + -2x = 16

Solving
10 + -2x = 16

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-10' to each side of the equation.
10 + -10 + -2x = 16 + -10

Combine like terms: 10 + -10 = 0
0 + -2x = 16 + -10
-2x = 16 + -10

Combine like terms: 16 + -10 = 6
-2x = 6

Divide each side by '-2'.
x = -3

Simplifying
x = -3

See similar equations:

| -23=4h-3 | | -100=x+20 | | 4x^2-21=-3x | | 7(x+2)-12=5(x+2)-12+16 | | 5-(-7)+2(-8)= | | 550-475= | | -5x+18=x+1 | | 9x^3-39x^2-27x+13=0 | | h=-16t^2+70+50 | | 10x+x=33 | | 13x+10x=9 | | 784/26/43 | | 2b+8=3b-2 | | C=19y+41 | | -x-1/2=2 | | 4(2-5y)+16=-76 | | 2x*30*7*100/39 | | 0.7k+1.4k+9.4=-1 | | 2h-1=45 | | K/-4=9 | | -2.6=-0.1p | | 3(2x+8)-x+5(x-x+5)-3x+1=24 | | 2x+9y=-82 | | 10*x^1/3=9 | | 3x^2-3=-6 | | -50=5w | | 15.7/x=0.7 | | 2x-4=3y+8 | | 3x+2-y=0 | | 2x-4+3y+8=5y+x+8 | | 9.25=-logx | | 720=3x+8y |

Equations solver categories